2021
DOI: 10.1002/tesq.3060
|View full text |Cite
|
Sign up to set email alerts
|

Funds of Professional Identity in Language Teacher Education: A Longitudinal Study on Student‐Teachers

Abstract: This article describes the professional identity formation of a group of pre‐service English as a foreign language student‐teachers at an initial English language teacher education program in Argentina. To this effect, a four‐year longitudinal study was designed drawing on the concept of funds of identity. Participants’ drawing of significant circles and interviews were used to document the main components of their funds of professional identity and the factors which informed their construction. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…So far, researchers have examined the construction of language teacher identity in diverse contexts, such as the classroom contexts ( Kanno and Stuart, 2011 ; Hiver and Whitehead, 2018 ), the broader institutional and social contexts ( Tsui, 2007 ; Wang and He, 2022 ), the online contexts ( Stranger-Johannessen and Norton, 2017 ; Chao, 2022 ), the educational innovation contexts ( Tao and Gao, 2018 ; Kessler, 2021 ; Dikilitaş and Bahrami, 2022 ), and various formal and informal learning contexts ( Trent, 2013 ; Yuan and Mak, 2018 ; Jeongyeon and Hye Young, 2020 ; Banegas et al, 2022 ). However, there has been a paucity of research attention on the construction of language teacher identity in study abroad contexts, although study abroad has generally been considered an important tool for teacher learning with positive outcomes for the professional development of language teachers, as the above review of relevant works has shown.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So far, researchers have examined the construction of language teacher identity in diverse contexts, such as the classroom contexts ( Kanno and Stuart, 2011 ; Hiver and Whitehead, 2018 ), the broader institutional and social contexts ( Tsui, 2007 ; Wang and He, 2022 ), the online contexts ( Stranger-Johannessen and Norton, 2017 ; Chao, 2022 ), the educational innovation contexts ( Tao and Gao, 2018 ; Kessler, 2021 ; Dikilitaş and Bahrami, 2022 ), and various formal and informal learning contexts ( Trent, 2013 ; Yuan and Mak, 2018 ; Jeongyeon and Hye Young, 2020 ; Banegas et al, 2022 ). However, there has been a paucity of research attention on the construction of language teacher identity in study abroad contexts, although study abroad has generally been considered an important tool for teacher learning with positive outcomes for the professional development of language teachers, as the above review of relevant works has shown.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While these two studies as well as others (e.g. Banegas, Pinner, and Larrondo 2022;Chu 2020;Trent 2013) provide comprehensive explications of student-teachers grappling with their professional identities in relation to past, present, and imagined social and individual experiences, they are solely focused on their identities as practitioners. This should not be surprising since that is the primary aim of initial teacher education programmes: to prepare teachers for teaching posts.…”
Section: Conceptual Framework (Student-) Teacher Identity Developmentmentioning
confidence: 99%
“…I see myself as a teacher who is capable of always learning. (Amira, Source 2, Extract 6) Extract 6 also attests to student-teachers' concern with their own English language proficiency and the hegemonic role that the native speaker has as a measure of their own confidence in language use (Banegas, Pinner, and Larrondo 2022;Lowe 2020;Richards 2021).…”
Section: Identity As Future Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher identity affects the quality of education, teacher preferences (Olsen, 2016) and teacher behavior management (Dugas, 2016); informs a teacher's decisions on instruction, content and their relationships with students (Beijaard et al, 2004) and mediates a teacher's actions (Chong et al, 2011). Additionally, providing opportunities for reflection might promote prospective language teachers' critical attitudes toward curriculum and language teaching strategies and their agency (Banegas et al, 2022). Although the literature focuses mostly on pre-service teachers (Henry, 2016;Varghese & Snyder, 2018), language teacher identity in non-Western contexts such as Turkey remains under-researched with scarce qualitative designs (Taşdemir, 2021).…”
mentioning
confidence: 99%